Exploring Coherence among Sri Lankan CFL Learners in Chinese-English Translation: Decoding and Interpreting of Culture-loaded Content - Dassanayake, Noel (International Journal of Language and Literary Studies, 2022)
Modern translation has shifted from its traditional approach of merely translating linguistic features towards a more culturally sensitive approach, which further considers the sociolinguistic spaces of the source text in producing the target text. This significant theoretical transformation has demanded the translator to play a more comprehensive role, which involves intercultural and sociolinguistic competencies apart from language competence. Subsequently, maintaining cohesion and coherence within and among texts also demands a heavier effort from the translator with neologisms being created frequently. The present study has been an attempt to identify the core issues pertaining to lexical coherence in translating from Chinese sources in Sri Lankan context using sample texts translated by Sri Lankan CFL (Chinese as a Foreign Language) learners. 20 culture-loaded lexical items were examined for coherence using a plagiarism checker and compared with Google and Baidu translation outputs of the source text. The results manifest that there is significant coherence among the target texts but coherence is a result of excessive use of machine translation, especially Google translate(?=94.67). 5-10 clusters were the most frequent clusters with an average of 21.73 clusters. < 10 word clusters have recorded an average of 19.07 whereas> 5 word clusters have recorded an average of 12.60.The highest number of clusters is recorded in text 5 with 44 clusters of <10 words. The highest number of translated variants of the same cultural term of the selected word list (n=20) is 4 while 70% (n=14) of the selected terms were only translated into either 1 or 2 variants. While machine translation is perceived as a constructive instrument under proper management, vigilant use of footnotes and end notes is perceived as a viable solution for reducing misinterpretation, vagueness and confusion in translating culture-loaded lexical items.